(untitled) (Raparin Journal of Humanities (RJH), 2020)
The Principality of Baban has a long history, which have been through many phases of power, falling, and rising, and along these phases its militaristic system from an era to the other and from a prince to another has changed to a point. But in general the concern of the princes of Baban in the field of military has not only been coherent, by some of them, but each who had the chance wanted to have a huge and powerful army to defend themselves and extend the borders of their Principality. That step has always been in the direction of opposing the Ottoman and Persian Empires, because these two empires never wanted the Principality of Baban to have an army and a prince that would be a threat to them. So in that case the Principality has always faced the charges and conspiracies of these two empires, either by direct charges or by tricking and using the members of the families of Baban Princes against each other, or creating struggle between the Kurdish Principalities. Furthermore, the geopolitic of the Principality of Baban, which was between the Ottoman and the Persian Empires, was a reason for the Principality to be the bordering struggles of both empires and make the Principality of Baban the arena of the liquidation of their contests, and face the instabilities of politics, economy, community, and military to the Principality. The tribal and feudalistic situation that was customary in Kurdistan, was effective in establishing the army of Principality of Baban, in a way that the soldiers and knights of the tribes were the backbone of the army.